Diagnosis and treatment of severe hemolytic disease of the fetus and newborn: a 10‐year nationwide retrospective study. (11th February 2015) - Sainio, Susanna; Nupponen, Irmeli; Kuosmanen, Malla; Aitokallio‐Tallberg, Ansa; Ekholm, Eeva; Halmesmäki, Erja; Orden, Maija‐Riitta; Palo, Pertti; Raudaskoski, Tytti; Tekay, Aydin; Tuimala, Jarno; Uotila, Jukka; et al.
Abstract Objective Outcome after intrauterine transfusions due to severe hemolytic disease of the fetus and newborn. Design Nationwide population‐based retrospective cohort study. Setting All women treated with intrauterine transfusions for hemolytic disease of the fetus and newborn in Finland in 2003–2012. Population 339 intrauterine transfusions, performed in 104 pregnancies of 84 women. Methods Information on antenatal screening of red cell antibodies and red cell units issued for intrauterine transfusion was obtained from the Finnish Red Cross Blood Service database, and obstetric and neonatal data from hospital records. Main outcome measures Procedure‐related complications, perinatal mortality, neonatal morbidity. Results Overall survival was 94.2% (95% confidence interval 89.7–98.7). There were four fetal and two neonatal deaths. Procedure‐related fetal loss rate was 1.2% (95% confidence interval 0.04–2.4) per procedure and 3.8% (95% confidence interval 0.1–7.5) per pregnancy. Of the four procedure‐related losses, three were due to technically difficult intrauterine transfusions causing infection and preterm birth. Of the live born infants, 19% (95% confidence interval 11.3–26.7) were born before 32 weeks' gestation. The incidence of severe neonatal morbidity (respiratory distress syndrome, severe cerebral injury, sepsis) was 22.2% (95% confidence interval 13.4–30.2). Poor outcome (death, severe neonatal morbidity) was negatively associated with gestational age at first transfusion (p = 0.001) and at birth (p = 0.00006). Follow‐up of the infants was too incomplete to assess the neurodevelopmental outcome. Conclusions Although overall survival is comparable with previous studies, our concern is procedure‐related infections and preterm births. Close collaboration between the university hospitals is needed to ensure timely treatment, operator skills and systematic follow‐up of the children.